The implication of ROS production on triflumuron-induced oxidative stress and genotoxicity in human colon carcinoma (HCT-116) cells. (15th June 2020) - Timoumi, Rim; Amara, Ines; Salem, Intidhar Ben; Buratti, Matia Franca; Testai, Emanuella; Abid-Essefi, Salwa
The aim of this study is to evaluate the cytotoxic and the genotoxic effects of triflumuron (TFM) on human colon carcinoma cells (HCT-116). Indeed, TFM is used to protect vegetables, fruits, and domestic animals against a large spectrum of parasites causing animal and human disorders. However, studies revealing its toxicity and its mode of action in mammalian systems remain very limited. We monitored our work with the cytotoxicity assay starting with the cell viability test, the ROS generation, the malondialdehyde (MDA) production, the DNA fragmentation, and the measurement of some antioxidant enzymes activities such as catalase, superoxide dismutase, and the glutathione S-transferase. Also, we measured the mitochondrial transmembrane potential. We showed that TFM induced a dose-dependent cell death. This decrease in cell viability was accompanied by a significant reduction in the mitochondrial membrane potential. We also have shown that TFM induced oxidative stress as revealed by the generation of reactive oxygen species, the increase of the MDA levels, and the activation of the antioxidant enzymes. Moreover, our results indicated that TFM induced DNA damage in HCT-116 cells as monitored by the comet assay. We demonstrate, for the first time, the cytotoxic and the genotoxic potentials of TFM on human cultured cells.